Validation of cytogenetic risk groups according to International Prognostic Scoring Systems by peripheral blood CD34(+)FISH: results from a German diagnostic study in comparison with an international control group - Braulke, Friederike (Haematologica, 2015)
International Prognostic Scoring Systems are used to determine the individual risk profile of myelodysplastic syndrome patients. For the assessment of International Prognostic Scoring Systems, an adequate chromosome banding analysis of the bone marrow is essential. Cytogenetic information is not available for a substantial number of patients (5%–20%) with dry marrow or an insufficient number of metaphase cells. For these patients, a valid risk classification is impossible. In the study presented here, the International Prognostic Scoring Systems were validated based on fluorescence in situ hybridization analyses using extended probe panels applied to cluster of differentiation 34 positive (CD34(+)) peripheral blood cells of 328 MDS patients of our prospective multicenter German diagnostic study and compared to chromosome banding results of 2902 previously published patients with myelodysplastic syndromes. For cytogenetic risk classification by fluorescence in situ hybridization analyses of CD34(+) peripheral blood cells, the groups differed significantly for overall and leukemia-free survival by uni- and multivariate analyses without discrepancies between treated and untreated patients. Including cytogenetic data of fluorescence in situ hybridization analyses of peripheral CD34(+) blood cells (instead of bone marrow banding analysis) into the complete International Prognostic Scoring System assessment, the prognostic risk groups separated significantly for overall and leukemia-free survival. Our data show that a reliable stratification to the risk groups of the International Prognostic Scoring Systems is possible from peripheral blood in patients with missing chromosome banding analysis by using a comprehensive probe panel (clinicaltrials.gov identifier:01355913).